Spory w relacjach transatlantyckich - Ziemborska, Liliana (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2012)
The Transatlantic Security Community, the mainstay of which is the North Atlantic Treaty Organization, has passed through a crisis repeatedly. At the beginning of the XXIst century the actions of the American Administration and a sceptical attitude of the Europeans towards the American war against terrorism caused an open con-flict between the allies from across the ocean. However, the tensions between military and political concepts of NATO have been increasing from the 1960’s. In the article entitled Disputes in transatlantic relations the most significant crises are raised, including the time of cold war, the 1990’s and the beginning of the XXIst century, when it came to a breach of Alliance which expressed the variable international conditions.
Disputes in Transatlantic Realtions
Keywords: Spory transatlantyckie; NATO; USA; Europa